(1307) Location of health services موقع الخدمات الصحية - Adel-Aziz, Medhat (معهد التخطيط القومى, 2020)
There is a wide spread belief that precise in sight and the use of effective techniques in the organization implementation, and evaluation of health services, is essential if higher standards of health care are to be achieved. Meanwhile the need for multidiscipline studies, making use of progress attained in knowledge and technology, both medical general, is unquestioned